The Impact of Integrated Psychological Services in a Safety Net Primary Care Clinic on Medical Utilization. Issue 6 (9th August 2016) - Lanoye, Autumn; Stewart, Karen E.; Rybarczyk, Bruce D.; Auerbach, Stephen M.; Sadock, Elizabeth; Aggarwal, Arpita; Waller, Rachel; Wolver, Susan; Austin, Kristin
Abstract : Objective: The integration of psychological and behavioral health services into safety net primary care clinics has been viewed as a step toward reducing disparities in mental health treatment and addressing behavioral factors in chronic diseases. Though it is posited that integrated behavioral health (IBH) reduces preventable medical costs, this premise has yet to be tested in a safety net primary care clinic. Method: Retrospective pre‐ and posttreatment analysis with quasi‐experimental control group was constructed using propensity score matching. Participants included 1, 440 adult patients at a safety net primary care clinic, 720 of whom received IBH services, and 720 of whom received medical treatment only. Results: Analysis showed that rates of preventable inpatient utilization decreased significantly among IBH‐treated patients compared to no change among control patients. Conclusion: IBH was associated with decreased rates of preventable inpatient visits. IBH may present opportunities to deliver improved holistic patient care while reducing unnecessary inpatient medical utilization.